Proceedings of the Twenty-Eighth Annual ACM-SIAM Symposium on Discrete Algorithms 2017
DOI: 10.1137/1.9781611974782.42
|View full text |Cite
|
Sign up to set email alerts
|

Computing Walrasian Equilibria: Fast Algorithms and Structural Properties

Abstract: We present the first polynomial time algorithm for computing Walrasian equilibrium in an economy with indivisible goods and general buyer valuations having only access to an aggregate demand oracle, i.e., an oracle that given prices on all goods, returns the aggregated demand over the entire population of buyers. For the important special case of gross substitute valuations, our algorithm queries the aggregate demand oracle O(n) times and takes O(n 3 ) time, where n is the number of goods. At the heart of our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…By the well known First Welfare Theorem (Nisan, Roughgarden, Tardos, & Vazirani, 2007, Theorem 11.13), whenever they exist, Walrasian equilibria maximize social welfare over all possible outcomes. It is also known (Kelso & Crawford, 1982;Leme & Wong, 2017) that a market with gross substitutes valuations always admits a Walrasian Equilibrium that can be computed in polynomial time and with a polynomial number of calls to the value oracle. Moreover, a market with unit-demand buyers (as Γ ) is a special case of a market with gross substitutes valuations in which the value oracle trivially requires polynomial time to be implemented, and therefore always admits a Walrasian Equilibrium that can be computed in polynomial time.…”
Section: Buyermentioning
confidence: 99%
“…By the well known First Welfare Theorem (Nisan, Roughgarden, Tardos, & Vazirani, 2007, Theorem 11.13), whenever they exist, Walrasian equilibria maximize social welfare over all possible outcomes. It is also known (Kelso & Crawford, 1982;Leme & Wong, 2017) that a market with gross substitutes valuations always admits a Walrasian Equilibrium that can be computed in polynomial time and with a polynomial number of calls to the value oracle. Moreover, a market with unit-demand buyers (as Γ ) is a special case of a market with gross substitutes valuations in which the value oracle trivially requires polynomial time to be implemented, and therefore always admits a Walrasian Equilibrium that can be computed in polynomial time.…”
Section: Buyermentioning
confidence: 99%
“…The efficiency guarantee for the minimal Walrasian prices was considered in [16] for both matching markets and matroid based valuations. 2 Interestingly, the question of finding a Walrasian equilibrium without ties in the demand for the case of gross substitutes valuations with a unique optimum was also asked by [21] in the quite different context of efficiently computing a Walrasian equilibrium given access to an aggregate demand oracle. For a survey on gross substitutes valuations, see [20].…”
Section: Related Workmentioning
confidence: 99%
“…Independently, Paes Leme and Wong[21] defined robust Walrasian pricing where there is no overlap between the demand sets of different buyers, and showed that for Gross substitute valuations with unique optima, such prices exist. Viewed from our perspective, this gives static prices that achieve optimal welfare for any order of arrival.…”
mentioning
confidence: 99%